Prevalence and Associated Factors of Inappropriate Dosing of Direct Oral Anticoagulants In Patients With Atrial Fibrillation: The ANATOLIA-AF Study (dec, 10.1007/s10557-022-07409-w, 2022) - Kocabas, Umut; Ergin, Isil; Yavuz, Veysel; Murat, Selda; Ozdemir, Ibrahim; Genc, Omer; Ozcalik, Emre (Springer, 2024)
[Abstract Not Available]